Arsenic removal from aqueous solutions by adsorption onto iron oxide/activated carbon magnetic composite - Yao, Shuhua (BioMed Central, 2014)
In this work the adsorption features of activated carbon and the magnetic properties of iron oxides were combined in a composite to produce magnetic adsorbent. Batch experiments were conducted to study the adsorption behavior of arsenate onto the synthetic magnetic adsorbent. The effects of initial solution pH, contact time, adsorbent dosage and co-existing anionic component on the adsorption of arsenate were investigated. The results showed that the removal percentage of arsenate could be over 95% in the conditions of adsorbent dosage 5.0 g/L, initial solution pH 3.0-8.0, and contact time 1 h. Under the experimental conditions, phosphate and silicate caused greater decrease in arsenate removal percentage among the anions, and sulfate had almost no effect on the adsorption of arsenate. Kinetics study showed that the overall adsorption rate of arsenate was illustrated by the pseudo-second-order kinetic model. The applicability of the Langmuir and Freundlich models for the arsenate adsorption data was tested. Both the models adequately describe the experimental data. Moreover, the magnetic composite adsorbent could be easily recovered from the medium by an external magnetic field. It can therefore be potentially applied for the treatment of water contaminated by arsenate.